Mucilage Problem in the Sea of Marmara - Albay, Meric (Istanbul University Press, 2023)
Lakes, rivers, and seas have been under the pressure of various pollutants, mostly of human origin, for more than centuries. These demands have increased enormously, particularly since the mid-1900s, when industrial production took the pace up, rendering many water resources unusable. Due to the deterioration in water quality and climate change, many species have disappeared or have faced extinction. Similar environmental problems have been observed in our country since the 1950s. Many water resources, especially the sea and inland water resources in the Marmara Region where most of the industrial production takes place, have suffered from industrial and domestic wastes and agricultural pollutants. The Marmara Sea is one of the areas that have the greatest loss of water quality because of these pollutants. The main cities in our country, especially Istanbul, the largest city, are located in the Marmara Sea basin, an inland sea. Despite being a relatively small area, the basin is host to approximately one-third of the country's population. Excessive population growth and uncontrolled construction in the basin have created great pressure on the Marmara Sea. For many years, the wastes were discharged to the Marmara Sea without any treatment or just with a pre-treatment. This has resulted from an exceeding the carrying capacity of the sea. Thus, many species living in the sea have completely disappeared. Fishing had been banned in the "East Bay" side of the Marmara Sea for many years due to excessive pollution. Recently, one of the most important environmental problems that have emerged in the Marmara Sea is mucilage formation, which lasts for around 6 months. The mucilage formation started in January 2021 and continued until June 2021. Since it was observed for 6 months, caused a habitat loss in a large area, issued economic problems, and affected many ecosystem services including fisheries, it has been featured in the international literature. Believing the necessity to investigate such an important ecological problem in detail and to reveal the results, Istanbul University decided to publish a book that consists of 13 chapters, including the studies only on the mucilage problem that emerged in the Marmara Sea. Our goal is for this publication by Istanbul University, which has nearly 80 years of marine research experience, to serve as a reference source for marine scientists and decision-makers.